Measuring Liquidity Risk in an Emerging Market: Liquidity Adjusted Value at Risk Approach for High Frequency Data - Emna, Rouetbi; Chokri, Mamoghli (International Journal of Economics and Financial Issues, 2013)
The present paper introduces an enhanced liquidity adjusted intraday value at risk measure named the LIVaR applied to a sample of listed securities in an emerging market; namely the Tunis Stock Exchange (BVMT). Very specific econometric tools were used to perform models that suit the statistical properties of the data and to obtain a more realistic and efficient measure. This methodology was applied to intraday data. It was found that in the BVMT, the liquidity risk is very high. It represents about 25% of the total cost supported by a day trader for the most active stocks of the considered sample. It can also reach more than 40% for the less liquid ones. These results reveal how thin the Tunis stock market is. Keywords: Liquidity; intraday value at risk; spread; ACD; Monte Carlo simulation. JEL Classifications: C41; G17